PENERAPAN MODEL THINK TALK WRITE DENGAN MULTIMEDIA DALAM PENINGKATAN HASIL BELAJAR BAHASA INGGRIS SISWA KELAS V SD NEGERI 2 SIDOMORO TAHUN AJARAN 2015/2016. - Khalimatun, Beti Dwi (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Think Talk Write Model Using Multimedia in Improving Learning Outcomes of English for the Fifth Grade Student of SD Negeri 2 Sidomoro in the Academic Year of 2015/2016. The objective of this research is to improve learning outcomes of English about vocabulary through the application of Think Talk Write model using multimedia. This collaborative classroom action research was conducted in three cycles. Subjects of this research were fifth grade students of SD Negeri 2 Sidomoro totaling 20 students. The results showed that the application of Think Talk Write model using multimedia can improve learning outcomes of English about vocabulary for the fifth grade students of SD Negeri 2 Sidomoro in the academic year of 2015/2016. Keywords: Think Talk Write, multimedia, English  Abstrak: Penerapan Model Think Talk Write dengan Multimedia dalam Peningkatan Hasil Belajar Bahasa Inggris Siswa Kelas V SD Negeri 2 Sidomoro Tahun Ajaran 2015/2016. Penelitian ini bertujuan untuk meningkatkan hasil belajar bahasa Inggris tentang kosakata melalui penerapan model Think Talk Write dengan multimedia. Penelitian tindakan kelas kolaboratif ini dilaksanakan dalam tiga siklus. Subjek penelitian ini adalah siswa kelas V SD Negeri 2 Sidomoro yang berjumlah 20 siswa. Hasil penelitian menunjukkan bahwa penerapan model Think Talk Write dengan multimedia dapat meningkatkan hasil belajar bahasa Inggris tentang kosakata pada siswa kelas V SD Negeri 2 Sidomoro tahun ajaran 2015/2016. Kata Kunci: Think Talk Write, multimedia, bahasa Inggris.